(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The preservation of languages and their transformation into a dead language depends on external conditions. Relations between languages are related to the geographical location of the people who speak it, and the culture, economy, customs, and psychology of the community. Some languages are spoken by very few people, while others are spoken by millions of people. The regional distribution of languages is also very diverse. For example, English and Spanish have regional variants spread across different continents and countries. Language variations that reflect local differences are called its dialects.